Cost Recovery for Variable-Speed Pumped Storage Power Plants in the Market Environment - Yonglai Li; Yue Fan; Xianbo Ke; Chao Huo; Ming Zhou; Yuxuan Yang; Jiaxing Wang; Yuhang Xin (Energies)
As the construction of the new power system progresses, pumped storage plays an important role in the system as a typical regulating resource. However, the regulating capacity of traditional fixed-speed pumped storage units is limited and it is difficult to meet the increasing flexibility demands of system regulation. This paper studies the operation and cost recovery of pumped storage power stations based on doubly-fed variable-speed technology in the market environment. Using a combination of theoretical analysis and case study, the working principles and technical advantages of doubly-fed variable-speed pumped storage technology are first explained. We then develop a revenue model encompassing both the energy and ancillary service markets and analyze the impact of different pricing mechanisms on cost recovery for variable-speed pumped storage power stations within the current situation of China’s electricity market. The research results indicate that under the combined effects of the electricity spot market and the ancillary service market, the flexibility value of variable-speed pumped storage power stations can be fully reflected, significantly increasing their revenues and enabling cost recovery and profitability. In the future, the pricing mechanisms of the electricity and ancillary service markets should be further improved, the functional positioning of pumped storage power stations should be optimized, and their support capabilities for the new power system should be enhanced.